Experimental study on emissions of algal biodiesel and its blends on a diesel engine - Yadav M.; Chavan S.B.; Singh R.; Bux F.; Sharma Y.C. (My University, 2025)
An laboratory-scale experimental study has been performed to evaluate the physicochemical characterization and exhaust gas emissions of algal oil methyl ester blends (biodiesel + diesel) and pure diesel fuel on a single cylinder, VCR diesel engine at varying load (0, 3, 6, 9 and 12 Kg) and CRs (13, 14, 15, 16 and 17) conditions. The algal oil obtained was transesterified using previously reported efficient catalyst potassium impregnated zinc oxide 60 K/ZnO-900 and methanol to synthesize methyl esters (AOMEs). Different AOMEs blends such as AB5, AB10, AB15, AB20, AB25, AB30, and AB50 were prepared with diesel fuel on the volume basis. All blended fuels were tested for important physicochemical properties such as density, calorific value, flash point and fire point as per ASTM standards and these blended fuels showed the comparable results within the test limit. Furthermore, exhaust emission analysis of HC, NOx, CO, CO 2 and O 2 gases of the prepared blends were performed and results were compared with baseline diesel fuel. Results showed that the AB30 blend exhibited the minimum exhaust emissions of pollutant gases. It reduces the emission of HC and CO gases up to 35.13 and 30%, respectively with an increase in NOx up to 25–30% due to presence of unsaturation moiety. The increased emissions of CO 2 and O 2 gases up to 9–20% and 8–20% were also observed due to oxygen content present in the blended fuel. In general trend, improved exhaust emissions were observed for AB30 at optimum parameter of 9 Kg load and CR 16 conditions that closely followed the standard diesel. © 2018 Taiwan Institute of Chemical Engineers